Regulasi Hukum Ruang Udara di Indonesia: Tantangan Penggunaan Drone dan Penerbangan Komersial - Ajah Mas Tati Yarti; Putri Demika Sinaga; Anindhita Firrizqi Kaurtania Putri (Jurnal Kajian Hukum dan Pendidikan Kewarganegaraan, 2026)
This study analyzes Indonesian airspace legal regulations related to the use of drones in the context of commercial aviation based on Law Number 1 of 2009 concerning Aviation and Minister of Transportation Regulation Number 37 of 2020, and identifies the need for more effective regulations and coordination between agencies such as the Ministry of Transportation, the Indonesian National Armed Forces (TNI), and the Indonesian National Police (Polri) to address the geographical challenges of an archipelagic country, safety risks, and national security threats. Using a normative juridical approach through a literature review of primary (regulations) and secondary (journals, reports) data, the results show that although Article 5 of Law No. 1/2009 affirms full air sovereignty and PM 37/2020 regulates drone operating limits (altitude 120 m, prohibition near airports 9 km), implementation is weak due to the lack of strict sanctions, radar technology, and synergy between agencies, as seen from drone incidents near airports and violations in border areas. The discussion highlights the urgency of Law No. Law No. 21 of 2025 concerning Airspace Management for AI-based UTM integration, operator education, and integrated oversight to maintain flight safety, public privacy, and sovereignty in the era of massive drones, with recommendations for regulatory revisions and a joint operations center.